The Influence of Leadership Style and Work Culture on Performance with Organizational Communication Mediation at the Agriculture, Fisheries and Food Office of Jembrana Bali Regency - I Made Suarnawa; Ni Ketut Dewi Irwanti; Ni Luh Putu Agustini Karta (PT FORMOSA CENDEKIA GLOBAL, 2026)
This research is motivated by the importance of improving employee performance as one of the determining factors for organizational success, which is influenced by various internal aspects, including leadership style, work culture, and organizational communication. This study uses a quantitative approach with the type of explanatory research. The population in this study is employees at the Jembrana Regency Agriculture, Fisheries and Food Office which is the object of research as many as 77 respondents. The data analysis technique used in this study is path analysis to test the direct and indirect influence between research variables. The results of this study show that leadership style affects the performance of employees of the Agriculture, Fisheries and Food Service of Jembrana Regency Bali. Work Culture affects performance. Organizational communication affects employee performance.